Mgtricity - a sustainable approach to electricity access - Carvalho, Raquel Rodrigues De (2020)
In this paper, context on electricity access around the world with a focus on the Sub-Saharan African region is given. To address this issue, MGtricity emerges with its third generation microgrid that aims to use solar power to provide electrical power to rural areas in the mentioned region.